Curriculum Guide for "In Search of the Oregon Trail." - Larson, Susan Booth; Nebraska Univ., Lincoln. GPN. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1997)
This curriculum guide for a PBS 2-part, 180-minute video, "In Search of the Oregon Trail" (narrated by Stacy Keach), provides information to help teachers develop lesson plans. The guide is comprised of 12 lessons incorporating 31 video chapters. Curriculum areas include history, geography, economics, sociology, ethnic studies, civics and government, science, environmental studies, mathematics, and language arts. Classroom activities can be adapted for grades 4-12. Included are key concepts addressed in the video chapters; discussion questions for the video chapters; in-depth lessons; related activities that teachers may use to extend their students' Oregon Trail study; related information, charts, and maps; and recommended resources for teaching about the Oregon Trail. The video program follows a general East-West path and is divided into video chapters that are grouped according to content. The guide contains brief content descriptions, time cues (indicating the number of minutes from the funding credits to the start of each part), the length of the video chapter, and key concepts and discussion questions for each chapter. A description of the relevant National Content Standards for "In Search of the Oregon Trail" can be found in the appendix. (BT)
Availability: GPN, P.O. Box 80669, Lincoln, NE 68501; Tel: 800-228-4630 (Toll Free); Fax: 800-306-2330 (Toll Free); E-mail: gpn@unl.edu.
Sponsoring Agency: Corporation for Public Broadcasting, Washington, DC.
ERIC Note: Videotape not available from ERIC.
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Keywords: Academic Standards; Elementary Secondary Education; Integrated Curriculum; National Standards; Social Studies; United States History; Oregon Trail; Guides, Classroom -- Teacher